Influência de fatores operacionais na formação de porosidade da soldagem MIG de alumínio - Morais, Fábio Campos (2001)
The aluminum alloys have lager application in the world-wide metallurgic industry. When welding aluminum alloys of series 5000, which are recognized as of good weldability, porosity formation in the weld bead is common to occur. Studies show that porosity is caused by hydrogen. In the aluminum welding, the hydro-carbons, water and hydrated oxides present on the plate surfaces, tum to be the largest hydrogen sources after having been “broken” at the entrance in the electric arc (liberating hydrogen). The objective of this work is to evaluate the influence of the plate surface conditions, prepared using different cleaning methods, metal transfer modes and different butt-joint groove preparations on the porosity levei of the aluminum MIG welded beads. The gravimetric and radiographic techniques were used on the quantitative assessment of the porosity levei, getting correspondence between the inspection methods. The relationship between the levei of the bead porosity and several modes of metal transfer, cleaning methods and joint configurations has been determined and classified in significance through the analysis of variance method. The results of the tests have shown significant influences of the metallic transfer mode and of joint configuration on porosity formation, yet no significant influence of the superficial cleaning method was found. The best results were obtained with pulsed controlled metal transfer in combination with a groove gap of 1.0 mm and using the back gas purging protection. Finally, tests with “dirty” as machined plate evidenced the real necessity of applying some type of cleaning on the aluminum plate before welding.